The virtual reality classroom: a randomized control trial of medical student knowledge of postpartum hemorrhage emergency management - Dunlop, Kristyn; Dillon, Grace; McEvoy, Aoife; Kane, Daniel; Higgins, Shane; Mangina, Eleni; McAuliffe, Fionnuala M. (Frontiers in Medicine, 2024)
Objective To investigate the use of a virtual reality learning environment (VRLE) to enhance medical student knowledge of postpartum hemorrhage (PPH) emergency management and insertion of a postpartum balloon. Methods A randomized control trial involving medical students from University College Dublin, Ireland. Participants were randomly allocated to the intervention group (VRLE tutorial) or control group (PowerPoint tutorial on the same topic). All participants completed pre-learning experience and post-learning experience surveys. Both groups were timed and assessed on postpartum balloon insertion technique on a model pelvis. The primary outcome was assessment of student knowledge. Secondary outcomes included confidence levels, time taken to complete the task, technique assessment, satisfaction with the learning environment, and side effects of VR. Results Both learning experiences significantly (p < 0.001) enhanced student performance on the post-learning experience multiple choice questionnaire, with no difference between the intervention and control groups. In the intervention group, time for task completion was significantly less compared to the control group (1–2 min vs. 2–3 min, p = 0.039). Both learning experiences significantly (p < 0.001) enhanced student confidence, with no significant difference between intervention and control groups. 100% of the students using the VRLE enjoyed the experience, and 82.4% were very likely to recommend use of VRLE in medical education. 94.1% of the students felt the VRLE was beneficial over didactic teaching. Conclusion Receiving formal instruction, regardless of format, enhances students’ knowledge and confidence of the topic covered. Students who received instruction via the VRLE assembled the postpartum balloon faster than students who received didactic teaching. VR may be beneficial in teaching hands-on procedural skills in obstetrics and gynecology education.